(untitled) (One Health & Risk Management, 2023)
Nowadays, many societies are facing a significant demographic shift, according to the WHO. As a result of this phenomenon, there is an imbalance of control leading to Elder Abuse, which is multidimensional. Unfortunately, recurrent elder mistreatment occurs in up to 80% of cases. Out of many types of violence and abuse, Neglect is the most common in our senior population, resulting in serious injuries and illnesses. Any signs of elder neglect such: poor personal hygiene, malnutrition, dehydration, luck of needed medical aids, untreated injuries or infections is an alarm for a prompt reaction of the responsible authorities, but also of society as a whole. One Health team is paving the own road towards success and its approach would consider diverse solutions for diverse needs for seniors to thrive: emotional, physical, social, intellectual, spiritual, cultural. A Chinese proverb is saying: “ An elderly person at home is like a golden treasure”. The “One Health and Risk Management” journal is an intellectual treasure, and also a great source of promoting the values of a healthy society.